2005
DOI: 10.1021/ja0554716
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Synthesis and Molecular Recognition of Phosphatase-Resistant Analogues of Phosphatidylinositol-3-phosphate

Abstract: The remodeling of phosphatidylinositol polyphosphates in cellular membranes by phosphatases and kinases orchestrates the signaling by these lipids in space and time. In order to provide chemical tools to study of the changes in cell physiology mediated by these lipids, three new metabolically-stabilized (ms) analogues of phosphatidylinositol-3-phosphate (PtdIns(3)P were synthesized. We describe herein the total asymmetric synthesis of 3-methylphosphonate, 3-monofluoromethylphosphonate and 3-phosphorothioate an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 63 publications
2
39
0
2
Order By: Relevance
“…Similar in vitro assays have also been conducted by an independent laboratory that used our mouse PIKfyve clone expressed by yeast plasmid [32]. Agreeably, our laboratory and that of Dr. Bob Michelle did not observe PtdIns5P when synthetic PtdIns3P substrate preparations were used in the in vitro assays, despite the great amounts of produced 32 P-PtdIns(3,5)P 2 [9,29,32] (illustrated in Fig. 2A).…”
Section: Enzymatic Routes In Intracellular Ptdins5p Productionsupporting
confidence: 63%
See 2 more Smart Citations
“…Similar in vitro assays have also been conducted by an independent laboratory that used our mouse PIKfyve clone expressed by yeast plasmid [32]. Agreeably, our laboratory and that of Dr. Bob Michelle did not observe PtdIns5P when synthetic PtdIns3P substrate preparations were used in the in vitro assays, despite the great amounts of produced 32 P-PtdIns(3,5)P 2 [9,29,32] (illustrated in Fig. 2A).…”
Section: Enzymatic Routes In Intracellular Ptdins5p Productionsupporting
confidence: 63%
“…PIKfyve was first implicated in PtdIns5P biosynthesis based on in vitro data from our laboratory, which revealed that native or recombinant PIKfyve preparations purified from various mammalian or insect cells synthesize PtdIns5P from PtdIns and PtdIns(3,5)P 2 , from PtdIns3P in the presence of [γ- 32 P]ATP [9,2931]. Substrate side chains play a key role in the efficiency of the in vitro kinase assay, with naturally occurring acyl chains being greatly preferred over the synthetic di-C 16 [9].…”
Section: Enzymatic Routes In Intracellular Ptdins5p Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 Here, 0.5 g of 1,2-O-dioctadecylrac-glycerol ͑0.83 mmol͒ and 0.32 mL diisopropylethylamine ͑1.8 mmol͒ were dissolved in 10 mL anhydrous dichloromethane at 0°C under a nitrogen atmosphere. Then, 0.25 g 2-cyanoethyl N, N-diisopropylchlorophosphoramidite ͑1.3 mmol͒ was added dropwise to the reaction, which was stirred at 0°C for 15 min, then at room temperature for 2 h. The crude product solution was washed with a 0.5 M solution of sodium bicarbonate, and the solvent evaporated.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously employed phosphorothioate and methylenephosphonates to prepare phosphatase-resistant analogues of phosphoinositides [8][9][10] and lysophosphatidic acid. [11] In each case, the analogues were less susceptible to acidic or enzymatic cleavage and some bound to cognate binding proteins with reduced affinity.…”
mentioning
confidence: 99%